Pengembangan Buku Saku Digital pada Topik B “Kondisi Perekonomian di Daerahku” untuk Kelas V Sekolah Dasar Kota Langsa: Penelitian - Sulistiani; Ronald Fransyaigu; Rapita Aprilia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop a digital pocket book as a learning medium for fifth-grade science education in elementary school. The research follows the Research and Development (R&D) model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection methods include observation, interviews, documentation, expert validation questionnaires, as well as response questionnaires from both students and teachers. The validation results show that the material expert provided a score of 92%, categorized as “very valid”, the language expert gave 86.6%, also deemed “very valid”, and the media expert rated it at 98%, falling under the “very valid” criteria. The teacher response questionnaire indicated a 100% score, classified as “very practical”, while the student response in the field trial also reached 100%, likewise rated as “very practical”. According to the paired sample t-test evaluation, a significance value of Sig < α (0.000 < 0.05) was obtained, indicating a significant improvement in student learning outcomes through the use of the digital pocket book. The study focused on the topic of identifying various types of creative economic activities in the local community, specifically for fifth-grade students in Langsa City.